Gender w edukacyjnym, publicznym dyskursie Kościoła. Analiza Listu pasterskiego na Niedzielę Świętej Rodziny - Kasiak, Mateusz (Kultura-Społeczeństwo-Edukacja, 2020)
Kasiak Mateusz, Gender in educational and public discourse of the Church. Analysis of the Pastoral Letter on the Sunday of the Holy Family. Culture – Society – Education no 2(16) 2019, Poznań 2019, pp. 289–312, Adam Mickiewicz University Press. ISSN 2300-0422. DOI 10.14746/kse.2019.16.19. Gender as a category of cultural gender and gender identity appears not only in scientific discourse as a topic of research, but also in public discourse, as a subject of various debates and disputes. This concept was also included into the discourse of the Catholic Church. Its creators – church leaders – embarked upon a public reinterpretation of the concept of gender, thus inserting their point of view into the broader political and ideological dispute. The aim of this paper is to review the postulates of the church concerning gender in the Pastoral Letter on the Feast of the Holy Family, which seems to be a leading programme paper concerning this issue. In this paper, gender as a research and scientific category is isolated from the scientific discourse and appropriated by the educational discourse of the church, where it functions as a scare tactic. Structural modifications in the text and style of the letter, stylistic and rhetorical tricks, as well as pragmatic mechanisms, make the text of the pastoral letter a persuasive political argument.